Alcaloides dos bulbos das espécies Griffinia gardneriana (Herb.) Ravenna e Habranthus itaobinus Ravenna (amaryllidaceae): perfil químico e propriedades citotóxicas e genotóxicas - Cole, Eduardo Roberto (2018)
The Amaryllidaceae family is widely distributed throughout the world, being considered one of the 20 most important families among which they present alkaloids in their composition, exhibiting antiviral, antimalarial, anticancer and anticholinesterase activities, among others. This work aims to perform a chemical study on alkaloids of Griffinia gardneriana and Habranthus itaobinus bulbs, belonging to this family, to evaluate its cytotoxic and genotoxic properties and the role of caspase-3 as a molecular mediator of apoptosis induced by these compounds. Fractions enriched in alkaloids obtained from G. gardneriana and H. itaobinus bulbs were initially subjected to gas chromatography coupled to mass spectrometry (GC-MS) and then fractionated by different chromatographic techniques, such as molecular exclusion chromatography, column chromatography and preparative thin layer chromatography. The isolation and identification of the alkaloids was done by means of high performance liquid chromatography and mono- and bidimensional nuclear magnetic resonance, in addition to circular dichroism. Studies were carried out to evaluate the cytotoxicity of the enriched fractions by the MTT method using the OVCAR-3, J774 and L929 cell lines. In addition, the in vitro cytotoxicity and genotoxicity of the alkaloids isolated (through the MTT assay and micronucleus test) using tumoral (HepG2, MCF- 7, A549) and normal (L929, CHO-1-15) cell lines. In parallel, a study was developed to evaluate the correlation of the results obtained in the cytotoxicity assays by MTT and cytometry by image analysis. Molecular docking studies were performed to evaluate the free binding energies between the alkaloids isolated with the caspase-3 protein, described in the literature as the probable site of action of these compounds, also being calculated the theoretical inhibition constant, Ki. The GC-MS result of the enriched fractions evidenced the presence of only one alkaloid in G. gardneriana and five in H. itaobinus. Seven alkaloids of Amaryllidaceae, belonging to different type skeletons, all of them already well characterized in the literature, are some common ones to the two species (trisphaeridine and pretazettine), whereas others present only in G. gardneriana (lycorine and sanguinine) or in H. itaobinus (tazettine, 11- hydroxyvitattine and 2-a-7-dimethoxyhomolycorine). All enriched fractions showed cytotoxic action in the tested methods, but for the alkaloids isolated 11-hydroxyvitattine and 2-a-7-dimethoxyhomocolycorine were not cytotoxic, whereas tazettine, trisphaeridine and sanguinine presented activity only against the fibroblastic lineage. Lycorine and pretazettine were 10 to 30 times more cytotoxic than the other alkaloids, being active also for the cancerous lines, exhibiting time-dependent and concentration action, besides being genotoxic and able to promote the apoptosis via caspase-3. This result corroborates the data obtained in the docking studies in which these two compounds were among those with the highest binding affinity values.